SGM Kelantan performs gymnastics at Universiti Malaysia Kelantan - Universiti Malaysia Kelantan, HEP (2010)
On March 9, 2012, sixteen members of the SGM Kelantan Gymnastics Group were invited to perform at the Chap Goh Meh festival (fifteenth day of the Lunar New Year) organised by the students of Universiti Malaysia Kelantan. This event was aimed at promoting Chinese culture to other races to promote harmony and mutual understanding.